Margaret Chase Smith Essay: The Right of Independent Thought - Fanton, Jonathan (Maine Policy Review, 2015)
This essay by Jonathan F. Fanton investigates the relationship between the humanities and the right of independent thought, as described by Senator Margaret Chase Smith in her “Declaration of Conscience” speech. The author suggests that independent thought must be renewed continually and cultivated at every turn, or it becomes fixed ideology that cannot adapt to changing circumstances.
Keywords: humanities; education; democracy